Curriculum development for translingual orientation: Teaching poetry writing in first-year Composition Courses - Liao, Fang-Yu (Universitas Ahmad Dahlan, 2023)
This study offers insights on developing poetry writing assignment in first-year composition courses for translingual orientation. Through a close examination of semi-structured interviews and students’ poems, the study aims to evaluatethe effectiveness of the teaching of poetry writing as translingual pedagogy in college English composition courses for both monolingual and multilingual students. Five monolingual and five multilingual students in this project experienced a three-week curriculum design to compose their poetry project in two different sections. The interview data shows that both monolingual and multilingual students acknowledge positive traits about the translingual pedagogy through a poetry writing assignment toward the end of the semester. The data also demonstrates that five monolingual students in this study value this poetry writing assignment with its invitation for being free and self-expressive, while the five multilingual students stress the practical outcomes, such as a personal breakthrough, poetry book as a concrete record of their life, or negotiation experiences. Furthermore, the study provides implications for developing curriculum design to enact translingual pedagogy based on students’ perceived difficulties and struggles.